# 3y+4(7-2y)-6(y+14)=-1-(y+5)

## Simple and best practice solution for 3y+4(7-2y)-6(y+14)=-1-(y+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 3y+4(7-2y)-6(y+14)=-1-(y+5) equation:

3y+4(7-2y)-6(y+14)=-1-(y+5)
We move all terms to the left:
3y+4(7-2y)-6(y+14)-(-1-(y+5))=0
We add all the numbers together, and all the variables
3y+4(-2y+7)-6(y+14)-(-1-(y+5))=0
We multiply parentheses
3y-8y-6y-(-1-(y+5))+28-84=0

We calculate terms in parentheses: -(-1-(y+5)), so:
-1-(y+5)
determiningTheFunctionDomain
-(y+5)-1
We get rid of parentheses
-y-5-1
We add all the numbers together, and all the variables
-1y-6
Back to the equation:
-(-1y-6)

We add all the numbers together, and all the variables
-11y-(-1y-6)-56=0
We get rid of parentheses
-11y+1y+6-56=0
We add all the numbers together, and all the variables
-10y-50=0
We move all terms containing y to the left, all other terms to the right
-10y=50
y=50/-10
y=-5

`